2018
DOI: 10.14740/jocmr3366w
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Urinary Neutrophil Gelatinase-Associated Lipocalin in Predicting Acute Kidney Dysfunction in Patients With Liver Cirrhosis

Abstract: BackgroundEarly detection of acute kidney dysfunction (AKD) in cirrhotic patients is crucial. Urinary neutrophil gelatinase-associated lipocalin (uNGAL) has been identified as an early marker of AKD. The aim of the study was to evaluate serial uNGAL as a marker and predictor of AKD in liver cirrhosis patients.MethodsSerial uNGAL and serum creatinine (sCr) levels were measured daily during the first 6 days of admission. Furthermore, sCr levels and the estimated glomerular filtration rate (eGFR) were measured af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Except for kidney biomarkers in blood species, those in urine species are also of clinical significance. Urinary neutrophil gelatinase-associated lipocalin (NGAL), an indicator of renal tubular damage, has been proposed as a biomarker of renal dysfunction [ 36 ] and a predictor of ACLF and mortality in liver cirrhosis [ 37 ]. However, urine NGAL was unavailable in the present study, and its impact on outcomes of cirrhotic patients with acute gastrointestinal bleeding could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Except for kidney biomarkers in blood species, those in urine species are also of clinical significance. Urinary neutrophil gelatinase-associated lipocalin (NGAL), an indicator of renal tubular damage, has been proposed as a biomarker of renal dysfunction [ 36 ] and a predictor of ACLF and mortality in liver cirrhosis [ 37 ]. However, urine NGAL was unavailable in the present study, and its impact on outcomes of cirrhotic patients with acute gastrointestinal bleeding could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It not only can be used to identify and diagnose the type of AKI in patients, but it is also conducive to the risk-stratification management of patients with liver cirrhosis during hospitalization. [ 20 , 28 , 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had already shown that NAFLD patients with CKD had a higher level of urine NGAL compared to non-CKD patients. 14,16,17 To our knowledge, our study was one of the first studies using urine NGAL as a predictor of CKD in patients with NAFLD. There is currently no reported cutoff value of urine NGAL in NAFLD patients for predicting CKD.…”
Section: Performance Of Urine Ngal For Predicting Ckd In Nafld Patientsmentioning
confidence: 91%
“…NGAL in urine indicates damage to the tubules and interstitium 14 . Some studies showed that in a group of CKD patients, the level of NGAL in the blood and urine is higher than in the non‐CKD group 14,16,17 . There were different cutoffs for urine NGAL among different studies.…”
Section: Introductionmentioning
confidence: 99%